Analgesic Effects of Dexmedetomidine and Remifentanil in Patients with Herniated Disc - Dalvandi, Mohsen; Amini Maleki, Taher; Kamali, Alireza; Nazemi Rafie, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The purpose of this study was to compare analgesic effects of dexmedetomidine with those of remifentanil in patients undergoing herniated disc surgery. Material and Methods: In this double-blind clinical trial study, 96 patients who were candidates for herniated disc surgery were enrolled. Patients were randomly divided into three groups with epidural block. In all three groups, leg and back pain were recorded within 2, 6, 12, and 24 hours after surgery. Patient sedation was recorded by Ramsay sedation score within 2, 6, 12, and 24 hours postoperatively. Data were analyzed by SPSS 20 software. Results: Foot pain and low back pain were lower in the dexmedetomidine-apotel group within 2 to 24 hours after surgery (p < 0.05). There was a statistically significant difference between the three groups in terms of sedation within 2 to 24 hours after surgery (p < 0.05). Furthermore, sedation was found to be higher in the apotel/normal saline group than the other two groups 2 to 6 hours after surgery. But no significant difference was observed between the dexmedetomidine-apotel and remifentanil-apotel groups (p < 0.05). Conclusion: Dexmedetomidine-apotel was capable of reducing back and leg pain in the postoperative period, but there is no difference between dexmedetomidine-apotel and remifentanil-apotel in sedation.